Appreciative inquiry : change at the speed of imagination - Watkins, Jane Magruder (Jossey Bass/Pfeiffer San FranciscoUS, 2001)
Advances the appreciative inquiry (AI) process as the way forward for organizational development practitioners who are committed to participative change. Looks at topics including: the rationale for a new approach to organizational change; definition, history,and theory of appreciative inquiry (AI); AI as a process (5 chapters); and, evaluation from an AI perspective.